2008
DOI: 10.5194/acp-8-6719-2008
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis of greenhouse gases over Europe measured by a network of ground-based remote FTIR instruments

Abstract: Abstract. This paper describes the statistical analysis of annual trends in long term datasets of greenhouse gas measurements taken over ten or more years. The analysis technique employs a bootstrap resampling method to determine both the long-term and intra-annual variability of the datasets, together with the uncertainties on the trend values. The method has been applied to data from a European network of groundbased solar FTIR instruments to determine the trends in the tropospheric, stratospheric and total … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(140 citation statements)
references
References 9 publications
4
130
0
Order By: Relevance
“…The division into 3 time periods is in agreement with dedicated trend change points defined and used for methane in earlier work (Dlugokencky et al, 2003Angelbratt et al, 2011). Our trend analysis is based on the approach described in Gardiner et al (2008). See Table 2 for the resulting figures.…”
Section: Sounding Techniquementioning
confidence: 68%
“…The division into 3 time periods is in agreement with dedicated trend change points defined and used for methane in earlier work (Dlugokencky et al, 2003Angelbratt et al, 2011). Our trend analysis is based on the approach described in Gardiner et al (2008). See Table 2 for the resulting figures.…”
Section: Sounding Techniquementioning
confidence: 68%
“…As p 1 p 2 represents the trend in molec/(cm 2 yr), the normalised (from now on called "relative") trend corresponds to the parameter p 2 , given in %/yr here. When calculating trends of stratospheric and tropospheric trace gases from measurements by FTIR instruments, Gardiner et al (2008) found that a third order Fourier series was the best balance between representing the time series and avoid over-fitting the data.…”
Section: Trend Analysis Methodsmentioning
confidence: 99%
“…The analysis is based on the approach described in Gardiner et al (2008). Briefly, the approach augments a basic linear trend model applied to the time series after substraction of a fitted intraannual function and uses least squares regression in conjunction with a bootstrap resampling of the residuals in order to determine confidence limits associated with the trend estimates.…”
Section: Iwv Trendsmentioning
confidence: 99%